Monometallic and bimetallic catalysts based on Pd, Cu and Ni for hydrogen transfer deoxygenation of a prototypical fatty acid to diesel range hydrocarbons - Cheah, K.W. (Elsevier B.V., 2020)
Bimetallic PdxNi(100-x) and PdxCu(100-x) structures of a wide compositional range supported on activated carbon were synthesised via a simple, cheap and commercially relevant method. The surface and bulk properties of both the bimetallic structures and their monometallic counterparts were determined via STEM-EDS, TEM, XPS, powder XRD, N2 porosimetry and ICP-OES. A close correlation between the XRD patterns and EDS elemental composition mapping of individual metal particles established the extent of palladium-base metal interaction in each sample. The performance of the different structures as catalysts for the selective hydrogenation and hydrodeoxygenation of oleic acid, a prototypical fatty acid, was evaluated using tetralin as a hydrogen donor. Catalysts displaying true bimetallic/alloy formation were found to improve the conversion of tetralin as compared to catalysts in which compositional segregation was observed. The PdxNi(100-x) series was found to outperform the PdxCu(100-x) catalysts in terms of hydrogen production via the dehydrogenation of tetralin, mirroring the fact that compositional segregation occurs more for the PdxCu(100-x) series than PdxNi(100-x). The hydrogen transfer deoxygenation of oleic acid over the monometallic and bimetallic catalysts was found to mirror the availability of hydrogen with those catalysts liberating more hydrogen also favouring the formation of C17 and C18 alkanes. Â© 2019 Elsevier B.V.